Breast Pathology Problematic Issues - Shousha, Sami.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book covers practical diagnostic issues in breast pathology, with special emphasis on areas which pose diagnostic difficulties. These include dealing with the gross specimens derived from patients treated with conservative surgery and those who had neo-adjuvant therapy before surgery. It also discusses how to deal with axillary lymph nodes, proliferative breast lesions, including DCIS, and problematic core biopsies, as well as fibro-epithelial, spindle cell, lobular, mucinous, metaplastic and papillary lesions, molecular classification of breast cancers, breast lesions in male patients and breast immunohistochemistry. There is a focus on unusual benign and malignant breast lesions and a large number of high-quality images help the reader diagnose difficult cases. Breast Pathology: Problematic Issues is aimed at histopathology consultants and senior trainees who deal with breast pathology.
Dealing with the gross specimen -- Handling Neo-Adjuvant therapy Specimens -- Proliferative Breast Lesions -- Problematic Core Biopsies -- Ductal Carcinoma in Situ -- Lobular neoplasia -- Grading of invasive carcinoma -- Fibroepithelial Lesions -- Mucinous Lesions of the breast and expression of WT1 -- Spindle cell lesions -- Papillary carcinomas -- Metaplastic breast carcinomas -- Metastatic lesions in the breast -- Axillary Lymph node biopsies -- A Practical Approach to the use of Immunohistochemistry in the Diagnosis and Management of Breast Disease -- Molecular classification and testing of breast carcinoma -- Uncommon benign breast lesions -- Uncommon malignant lesions -- Male breast lesions.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology